Unraveling Unlawful Command Influence - Monu Bedi (Washington University Law Review, 2016)
Military commanders are not just officers leading soldiers into battle. In the military justice system, they also serve quasi-prosecutorial roles and decide what charges to bring and whether to accept a plea. With this responsibility comes the potential for misconduct, no different than with civilian prosecutors. Commanders too can improperly coerce witnesses or withhold favorable evidence. Enter the “unlawful command influence” doctrine, the military’s response to combating this misconduct. While routinely associated with civilian prosecutorial misconduct, the military standard turns out to be very different and seems to better protect against improper influence than its civilian counterpart. What accounts for this difference, given that both standards are designed to ensure a fair and impartial trial? This Article is the first to raise this varying treatment and explore potential explanations. It ultimately teases out the concepts of “systemic integrity” and “individual autonomy” from the respective stories. The military’s focus on procedural protections and concern for the appearance of impropriety reveals a value for systemic integrity, whereas the civilian emphasis on defendant choice and finality of proceedings reveals a value for individual autonomy. This is not simply an academic exercise. These concepts can help frame current controversies surrounding prosecutorial and commander discretion. On the civilian side, scholars and judges alike have widely criticized courts for not doing enough to combat prosecutorial misconduct. On the military side, legislators have railed against commanders for their lack of prosecution of sexual assault crimes. Recognizing which value—individual autonomy or systemic integrity—underlies these practices can better assist necessary reforms.
Keywords: military; unlawful command influence; prosecution; UCMJ